2022
DOI: 10.1101/2022.06.30.497950
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brain dynamics predictive of response to psilocybin for treatment-resistant depression

Abstract: Psilocybin therapy for depression has started to show promise, yet the underlying causal mechanisms are not currently known. Here we leveraged the differential outcome in responders and non-responders to psilocybin (10mg and 25mg, 7 days apart) therapy for depression - to gain new insights into regions and networks implicated in the restoration of healthy brain dynamics. We used whole-brain modelling to fit the spatiotemporal brain dynamics at rest in both responders and non-responders before treatment. Dynami… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…The important role of 5‐HT 2A receptor agonism in psychedelics’ mechanism of action is widely agreed upon 67–70,73,74 . Recent examination of brain regions involved in response to psilocybin‐based therapy for depression showed brain regions associated with restoration of healthy brain function to overlap significantly with 5‐HT 2A and 5‐HT 1A receptor affinity maps 75 . Research has shown dense presentation of 5‐HT 2A receptors in regions of the brain associated with music perception and music‐evoked emotion 76 .…”
Section: Common Brain Network In Music and Psychedelicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The important role of 5‐HT 2A receptor agonism in psychedelics’ mechanism of action is widely agreed upon 67–70,73,74 . Recent examination of brain regions involved in response to psilocybin‐based therapy for depression showed brain regions associated with restoration of healthy brain function to overlap significantly with 5‐HT 2A and 5‐HT 1A receptor affinity maps 75 . Research has shown dense presentation of 5‐HT 2A receptors in regions of the brain associated with music perception and music‐evoked emotion 76 .…”
Section: Common Brain Network In Music and Psychedelicsmentioning
confidence: 99%
“…[67][68][69][70]73,74 Recent examination of brain regions involved in response to psilocybin-based therapy for depression showed brain regions associated with restoration of healthy brain function to overlap significantly with 5-HT 2A and 5-HT 1A receptor affinity maps. 75 Research has shown dense presentation of 5-HT 2A receptors in regions of the brain associated with music perception and music-evoked emotion. 76 In fact, 5-HT 2A receptor signaling under LSD led to a biased neural response to music stimuli when compared to placebo as well as when compared to pretreatment with a 5-HT 2A antagonist.…”
Section: Common Brain Network In Music and Psychedelicsmentioning
confidence: 99%
“…Complimentarily, other measures describing brain states in terms of dynamical system's theory can be considered, such as the Probabilistic Metastable Substates shown to capture differences between sleep stages 36 and distinguish responders and non-responders to psilocybin treatment to depression 49 . Alternatively, novel methods from non-equilibrium and turbulent systems have been considered to further expand the notion of a brain state for future in-silico exploration for the Dynamic Sensitivity Analysis 8,50 .…”
Section: Discussionmentioning
confidence: 99%
“…After running the clustering for all the values of k we focused our analysis on k=3, which resulted in the minimal number of substates to reflect differences between conditions SCZ and HC. In addition, k=3 has been shown in previous research to offer a good characterisation of brain dynamics (Deco et al 2019;Escrichs et al 2022;Vohryzek et al 2022). It allows to reach a good balance between informativity and synthesis, important to increase meaningful interpretability of the results by focusing on the most relevant dynamics.…”
Section: Definition Of Probabilistic Metastable Substatesmentioning
confidence: 95%
“…To do so, we adapted a pipeline recently developed by our group (Deco et al 2019) which effectively detects critical areas involved in different altered states (Escrichs et al 2022; Vohryzek et al 2020, 2022), to investigate the mechanism of altered brain function in schizophrenia. To this aim we applied the workflow of analysis described in Fig.…”
Section: Introductionmentioning
confidence: 99%